The Impact of Smoke From Vegetation Fires on Sensory Characteristics of Cabernet Sauvignon Wines Made From Affected Grapes - de Vries, C.J.; Buica, A.; Brand, J.; McKay, M. (South African Journal of Enology and Viticulture, 2016)
The increased incidence of vegetation fires near vineyards in the Western Cape, South Africa has led to growing concern over smoke taint in wine made from affected grapes. This study focused on the sensory properties of wines made from grapes that have been exposed to bushfire smoke. Cabernet Sauvignon grapes (ten days’ post-véraison) were exposed to a single, hour-long treatment with smoke from burning fynbos under controlled conditions. The grapes were allowed to ripen and wines were then produced. Descriptive analysis of the wines was done for aroma and taste attributes. The results of the investigation show that the exposure of grapes to smoke during ripening led to sensory differences between wines made from different treatments, and that wines made from smoke-exposed grapes were perceived as having ‘burnt’, ‘smoky’ aromas and an ‘ashy’ aftertaste. Despite levels of free volatile phenols (VPs) being below or close to odour threshold levels for individual phenols, their combination led to a perception of the socalled ‘burnt rubber’ taint perceived in some South African red wines.